2020
DOI: 10.1097/fjc.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Sulodexide Improves Contraction and Decreases Matrix Metalloproteinase-2 and -9 in Veins Under Prolonged Stretch

Abstract: High pressure in the lower-limb veins is often associated with chronic venous insufficiency and varicose veins (VVs), making it important to search for the mechanisms and agents that control venous function. We have shown that protracted increases in venous stretch/wall tension reduce vein contraction and augment matrix metalloproteinase (MMP)-2 and -9. Also, MMP-2 and MMP-9 promote venodilation, a hallmark of VVs. Sulodexide (SDX) is a blend of glycosaminoglycans with efficient profibrinolysis and antithrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…Sulodexide’s effect on venous contraction was partly due to an increase in the sensitivity of the α-adrenergic receptor, but likely, sulodexide also enhanced downstream mechanisms (Ca 2+ sensitivity and mobilization, PKC, MAPK, and Rho-kinase). These novel mechanism in SDX vein contraction may be important not only in venous leg ulcers but also in treating CVD in general and improving venous function [ 170 , 171 ].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Sulodexide’s effect on venous contraction was partly due to an increase in the sensitivity of the α-adrenergic receptor, but likely, sulodexide also enhanced downstream mechanisms (Ca 2+ sensitivity and mobilization, PKC, MAPK, and Rho-kinase). These novel mechanism in SDX vein contraction may be important not only in venous leg ulcers but also in treating CVD in general and improving venous function [ 170 , 171 ].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“… 14 The structural and functional diversity of MMPs rival those of the collagen superfamily, and MMP‐2 has a prominent role in vascular remodelling. 15 , 16 , 17 The proteolytic activity of MMP‐2 is regulated at three levels: first—via expression and secretion; second—through pro‐enzyme activation and third—through inhibition by tissue inhibitors of MMPs (TIMPs). This regulation serves to maintain a delicate balance.…”
Section: Introductionmentioning
confidence: 99%
“…4,122,123 Besides accelerating the epithelialization of refractory trophic ulcers, protects the endothelium, preventing endothelial venous cell apoptosis and inhibiting the release by endothelial cells of reactive oxygen species (ROS) and pro-inflammatory chemokines and interleukins, sulodexide also is able to inhibit MMPs with cysteine residues such as MMP-2 and MMP-9 as in-vitro and in-vivo experiments have shown. 16,124126 The above mentioned properties of sulodexide together with hemodynamic properties allow patients treated with sulodexide to have improved CVD symptoms and achieve healing of venous ulcers. 12,112,127–131 The meta-analysis of observational studies reported in this work (Supplementary Appendix 4, Figures 1 to 8), as already shown in previous studies, 15 confirmed the expected effectiveness of sulodexide in improving symptoms, signs and indirectly the quality of life of patients with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, a new experimental study in rats demonstrated that sulodexide increased contractility and restoration of vein function inducing decrease of MMP-2 and MMP-9 endothelial levels after prolonged stretch. 16…”
Section: Introductionmentioning
confidence: 99%